Ocenka adaptacionnogo potenciala serdecno-sosudistoj sistemy kon'kobežcev v godicnom makrocikl - Martynenko, I. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2019)
In article techniques of control of a medico-biological component of training and competitive process of skaters, the includingvariability of a warm rhythm and a power state are described. It allows the expert or the trainer to conduct independently the analysis of a set of functional systems of an organism of the athlete, both during training process, and after it for tracking of quality of restoration. The offered system of control methods promotes effective implementation of training and competitive processes and also that is much important, promotes preservation of the contingent of engaged.